(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article analyzes the scientific approaches to understanding the concept of «competitiveness» and determined that one of its components is the financial competitiveness. The authors noted that the financial competitiveness is determined by financial stability, solvency, capital turnover rate, profitability and return on sales of goods and profitability of assets of business entities. The paper formulates basic financial characteristics typical enterprise competitiveness and generalized method of estimation of the integral index of competitiveness of businesses. An integrated analysis of financial competitiveness of the food industry and identified indicators that affect the effective rate.